Pengaruh Peran (P4S) Tranggulasi Dalam Meningkatkan Keberdayaan Petani Desa Batur, Kecamatan Getasan, Kabupaten Semarang (The Influence of the Role (P4S) of Trangulation in Increasing the Empowerment of Farmers in Batur Village, Getasan District, Semarang Regency) - Lestari, Eko Binti; Nurlaela, Siti; Mastur, Mastur (Jurnal Ilmiah Sosio Agribis, 2025)
The Independent Rural Agricultural Training Center (P4S) plays a strategic role in enhancing farmers' empowerment through various training programs, mentoring, and strengthening agricultural business networks. This study aims to analyze the impact of P4S Tranggulasi’s role on the level of farmers' empowerment in Batur Village, Getasan District, Semarang Regency. The role of P4S in this study consists of four main variables: training, consultancy function, farmer regeneration, and business network development. Farmers' empowerment is measured based on three main aspects: technical farming skills, business management skills, and market access and marketing capabilities. This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to farmers involved in P4S Tranggulasi programs and analyzed using multiple linear regression to determine the influence of each variable on farmers' empowerment. The results indicate that, simultaneously, the role of P4S has a significant impact on farmers' empowerment. The variables of farmer regeneration and business network development have a significant influence on improving technical farming skills, business management, and market access and marketing. The empowerment strategy through P4S needs to be optimized, particularly in the aspects of farmer regeneration and strengthening business networks, to enhance the competitiveness and sustainability of agricultural enterprises.Keywords: The Role of P4S Tranggulasi, Farmer empowerment, multiple linear regression